Stakeholder engagement in sustainable practices at live music festivals - Mindermann, Rieke (2024)
This thesis explores stakeholder engagement in sustainable practices at live music festivals, focusing on key stakeholders identified by the Business Project (BP): festival organizers, vendors, sponsors, performers, music labels, attendees, workers, Non-Governmental Organizations (NGOs) and local communities. Using stakeholder theory and qualitative interview analysis, identified key factors impacting stakeholder engagement include Education and Awareness, Convenience and Accessibility, Incentives and Rewards, Collaboration and Partnerships, Guidelines and Standards and Transparency and Reporting. Findings emphasize the need for educational programs, clear communication channels, nudges and convenience. This study offers academic insights and practical guidelines to promote sustainability in the live music industry.